HUBUNGAN DOMINASI SATELIT ANTARIKSA AMERIKA SERIKAT TERHADAP AKTIVITAS KEANTARIKSAAN CHINA MELALUI PROYEK KONSTELASI STARLINK 2018-2021 - Begawan Gita EPT, (2023)
This study looked at how Starlink's dominance of satellites in space was one of the efforts to implement U.S. national interests in space. The Starlink constellation project attracted much attention from many parties, due to its rapid and steady growth, not least China. China is the second country after the United States, which has the most satellites in orbit, as well as a country with no less advanced space technology. To support this analysis, researchers used the theory of space security and national interest. Space security theory researchers use to discuss the current state of space that is no longer safe and peaceful. While national interest theory, researchers use it to discuss what is in the interests of two powerful countries, the United States and China. This study used descriptive qualitative methodology. From an analysis study, researchers found Starlink played a considerable role in America's national interests in space, as well as how it relates to China's aerospace activities. Outer space becomes a space to project the power of each country.